Advancing Key Gaps in the Knowledge of Plasmodium vivax Cryptic Infections Using Humanized Mouse Models and Organs-on-Chips - Aparici Herraiz, Iris; Caires, Hugo R.; Castillo-Fernández, Óscar; Sima, Núria; Méndez-Mora, Lourdes; Risueño, Ruth M.; Sattabongkot, Jetsumon; Roobsoong, Wanlapa; Hernández-Machado, Aurora; Fernandez-Becerra, Carmen; Barrias, Cristina C.; del Portillo, Hernando A. (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium vivax is the most widely distributed human malaria parasite representing 36.3% of disease burden in the South-East Asia region and the most predominant species in the region of the Americas. Recent estimates indicate that 3.3 billion of people are under risk of infection with circa 7 million clinical cases reported each year. This burden is certainly underestimated as the vast majority of chronic infections are asymptomatic. For centuries, it has been widely accepted that the only source of cryptic parasites is the liver dormant stages known as hypnozoites. However, recent evidence indicates that niches outside the liver, in particular in the spleen and the bone marrow, can represent a major source of cryptic chronic erythrocytic infections. The origin of such chronic infections is highly controversial as many key knowledge gaps remain unanswered. Yet, as parasites in these niches seem to be sheltered from immune response and antimalarial drugs, research on this area should be reinforced if elimination of malaria is to be achieved. Due to ethical and technical considerations, working with the liver, bone marrow and spleen from natural infections is very difficult. Recent advances in the development of humanized mouse models and organs-on-a-chip models, offer novel technological frontiers to study human diseases, vaccine validation and drug discovery. Here, we review current data of these frontier technologies in malaria, highlighting major challenges ahead to study P. vivax cryptic niches, which perpetuate transmission and burden.